2007
DOI: 10.1016/j.febslet.2007.02.016
|View full text |Cite
|
Sign up to set email alerts
|

mGluR1 in the fundic glands of rat stomach

Abstract: L L-glutamate not only confers cognitive discrimination for umami taste in the oral cavity, but also conveys sensory information to vagal afferent fibers in the gastric mucosa. We used RT-PCR, western blotting, and immunohistochemistry to demonstrate that mGluR1 is located in glandular stomach. Double staining revealed that mGluR1 is found at the apical membrane of chief cells and possibly in parietal cells. Moreover, a diet with 1% L L-glutamate induced changes in the expression of pepsinogen C mRNA in stomac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 27 publications
2
72
1
5
Order By: Relevance
“…For example, neuronal glutamate receptors such as metabotropic glutamate type 1 (mGluR1) and type 4 (mGluR4) are expressed in the taste cells on the tongue 1 3) as well as mucosal cells in the stomach and duodenum 4,5) . Sweet taste receptors (T1R2/T1R3) and umami taste receptors (T1R1/ T1R3) for sensing amino acids on the tongue have also been indicated to be distributed in the intestine.…”
Section: Amino Acid-sensing Receptors Distrib-uted In the Taste And Gmentioning
confidence: 99%
“…For example, neuronal glutamate receptors such as metabotropic glutamate type 1 (mGluR1) and type 4 (mGluR4) are expressed in the taste cells on the tongue 1 3) as well as mucosal cells in the stomach and duodenum 4,5) . Sweet taste receptors (T1R2/T1R3) and umami taste receptors (T1R1/ T1R3) for sensing amino acids on the tongue have also been indicated to be distributed in the intestine.…”
Section: Amino Acid-sensing Receptors Distrib-uted In the Taste And Gmentioning
confidence: 99%
“…Infusion of amino acids into the intestine has been shown to increase vagal afferent activity and antroduodenal contraction (25). Interestingly, two groups of researchers have reported that T1Rs and mGluR1, receptors mediating the umami taste in the oral cavity, are expressed in the GI mucosa of humans, rats, and mice (26,27). Intragastric administration of L-glutamate increases the firing rate of afferent fibers running in the gastric branch of the vagus nerve in rats (28).…”
mentioning
confidence: 99%
“…mGluR4 is localized at low expression levels in the rat jejunum (14). In contrast, mGluR1 is located in the chief cells (pepsinogen-secreting cells) of the rat stomach (15). In addition, some mGluRs and amino acids sensors are expressed in gastric mucosal cells using cell fractions isolated from rats (16,17).…”
Section: Gut Nutrient Stimuli Regulate Autonomic Nervous System Activitymentioning
confidence: 99%